The information content of stress test announcements - Guerrieri, Luca; Modugno, Michele (Journal of Banking & Finance, 2024)
We exploit institutional features of the U.S. bank stress tests to disentangle different types of information garnered by market participants when the stress test results are released. By examining the reaction of different asset prices, we find evidence that market participants value the stress test announcements not only for the information on possible future capital distributions but also for the signals about bank resilience. These results back the use of stress tests by central banks to inform the broader public about the soundness of the banking system.